Pengaruh Politik Uang dan Status Sosial Ekonomi terhadap Partisipasi Masyarakat dalam Pemilihan Legislatif 2019 - Martinus Laia; Heri Kusmanto; Warjio Warjio (PERSPEKTIF, 2021)
In the 2019 simultaneous general elections held throughout Indonesia, the level of community participation in the lolomatua sub-district, Kabuparen South Nias, especially in the legislative elections reached 76% who had exercised their voting rights. This study aims to analyze the influence of money politics and socio-economic status on the level of participation. The theories used to explain the problems in this study are money politics, political exchange, political behavior, rational choice, socioeconomic status and participation. Furthermore, the research method used is a quantitative method with a descriptive approach which intends to explain the causal relationship and the influence between variables through hypothesis testing. The number of samples in this study were 100 respondents with a margin of error (error margin) of 10%. In the 2019 legislative elections, especially in the Lolomatua sub-district, money politics and the level of community participation had a positive influence and had a significant effect and the socio-economic status and level of participation had a positive and significant impact. Furthermore, the magnitude of the influence of money politics and socio-economic status together / simultaneously is 57%, which means that it has a strong influence on the level of public participation in voting.